Mapping a Multiple Frameworks for Financing Literacy in Nigeria (2019)
UNESCO (2009) contends that “literacy is still one of the most neglected education goals in many countries, especially among the poorest nations”. This is reflected in the poor financial allocation to it in many poorest nations, especially African countries with particular reference to Nigeria. Besides, there is a lack of a holistic framework for financing literacy in the country. This paper, therefore, advocates the urgent need for the adoption of multiple sources of financing literacy in Nigeria and therefore maps out the framework for achieving this advocacy. The paper begins with the discussion on problems of financing literacy in Nigeria. It provides justification for multiple sources of financing literacy in the country and thereafter discusses the experiences of other lands in financing literacy. The framework for achieving multiple sources of financing literacy in Nigeria is also discussed. The paper was rounded-off with the submission that financing literacy in Nigeria should be the business of all. Therefore, no one should be left out in financing literacy to ensure its sustainability in Nigeria